VD_FINDINFO HC / 2012 / 515 vom 2. August 2012 - VD Tribunal cantonal (2012)
DROIT À LA PRESTATION D'ASSURANCE, INDEMNITÉ JOURNALIÈRE, ASSURANCE COLLECTIVE | 2 al. 1 CC, 156 CO, 97 CO, 267 CPC, 335 CPC, 340 al. 1 CPC, 46 al. 1 LASV, 46 al. 2 LASV, 85 al. 2 LSA, 106 LPA-VD, 108 al. 1 LPA-VD, 109 al. 2 LPA-VD, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 313 al. 1 CPC (CH), 7 CPC (CH)